Progenitor cell therapy for acquired pediatric nervous system injury: Traumatic brain injury and acquired sensorineural hearing loss. (9th October 2020) - Baumgartner, James E.; Baumgartner, Linda S.; Baumgartner, Michael E.; Moore, Ernest J.; Messina, Steven A.; Seidman, Michael D.; Shook, David R.
Abstract: While cell therapies hold remarkable promise for replacing injured cells and repairing damaged tissues, cell replacement is not the only means by which these therapies can achieve therapeutic effect. For example, recent publications show that treatment with varieties of adult, multipotent stem cells can improve outcomes in patients with neurological conditions such as traumatic brain injury and hearing loss without directly replacing damaged or lost cells. As the immune system plays a central role in injury response and tissue repair, we here suggest that multipotent stem cell therapies achieve therapeutic effect by altering the immune response to injury, thereby limiting damage due to inflammation and possibly promoting repair. These findings argue for a broader understanding of the mechanisms by which cell therapies can benefit patients. Abstract : Injury to the central nervous system and ear lead to immediate neuron and hair cell loss (green), respectively. Neuron/hair cell loss continues over subsequent months, exacerbating neurological impairments. Recent studies indicate this could result from chronic inflammation and unresolved proinflammatory signals (red). Treatment with mesenchymal progenitor cells (blue) improves neuron/hair cell survival, potentially via anti-inflammatory mechanisms.